Applications of numerical methods in design and evaluation of overtopping protection systems - Salazar, F., author; San Mauro, J., author; Larese, A., author; Irazábal, J., author; Morán, R., author; Oñate, E., author; Toledo, M. Á., author; Colorado State University. Department of Engineering, publisher (Colorado State University. Libraries, 2016)
The development of overtopping protection systems often requires detailed analyses of complex physical phenomena. This hinders the comprehensive knowledge of their behavior, and therefore the development of suitable design criteria. In recent years, the authors have developed and validated different methods, combining continuous, particle and discrete numerical techniques, to obtain accurate and reliable solutions of different numerical problems involving fluid-soil-structure interaction. In this contribution, some applications of these methods to the study of dam protection against overtopping are presented. The main advantages of this approach include the ability to extract results of the governing variables (pressure, velocity) at any location of the domain, and the possibility to consider scenarios without the restrictions of the experimental facilities (flow rates, size, scale effects). In particular, the contribution gathers examples of application of numerical methods in a) analysis of rockfill dam stability against overtopping, including seepage evolution and deformation of the downstream shoulder, and b) stability analysis of wedge-shaped-blocks subjected to vandalism.
Presented at the Protections 2016: 2nd international seminar on dam protection against overtopping: concrete dams, embankment dams, levees, tailings dams held on 7th-9th September, 2016, at Colorado State University in Fort Collins, Colorado, USA. The increasing demand for dam and levee safety and flood protection has motivated new research and advancements and a greater need for cost-effective measures in overtopping protection as a solution for overtopping concerns at levees and dams. This seminar will bring together leading experts from practice, research, development, and implementation for two days of knowledge exchange followed by a technical tour of the Colorado State University Hydraulic Laboratory with overtopping flume and wave simulator. This seminar will focus on: Critical issues related to levees and dams; New developments and advanced tools; Overtopping protection systems; System design and performance; Applications and innovative solutions; Case histories of overtopping events; Physical modeling techniques and recent studies; and Numerical modeling methods.
Keywords: numerical modeling; spillways; wedge-shaped blocks; overtopping protection; rockfill dams; fluid-soil-structure interaction